Turbulence, empowerment and marginalisation in international education governance systems - Taysum, Alison; Arar, Khalid (Studies in educational administration, 2018)
This book investigates how governance at different levels can improve access to education for excluded communities. It conceptualises turbulence, empowerment, and marginalisation in international educational governance systems, and presents a comparative analysis of five nation states (England, Arabs in Israel, Northern Ireland, Trinidad and Tobago, and the United States). From these carefully-selected case studies, readers are shown how Senior Level Leaders describe turbulence in their systems - and how they articulate both the kind of support they want, and the support they actually get at the infrastructural, resources and agency level. It shows how the Senior Leaders hope to put their track records in school improvement into action in order to mobilise school communities for Empowering Young Societal Innovators for Equity and Renewal. Based on research that is world leading in terms of originality, significance, and rigour, 'Turbulence, Empowerment and Marginalisation in International Education Governance Systems' is both a comprehensive investigation of the question of how systems empower key agents of change in school communities, and a practical guide to how these communities can become societal innovators for equity, peace and renewal.